Communication anxiety among non-native Chinese learners: practice and reflections on task-based language teaching (TBLT) / Lew Ya Ling, Wong Hoong Cheong and Naginder Kaur - Lew, Ya Ling; Wong, Hoong Cheong; Kaur, Naginder (Akademi Pengajian Bahasa, 2021)
In Malaysia, many non-native Chinese learners suffer lack of confidence when communicating with native Chinese speakers, despite successfully completing Chinese as a Foreign Language course at the university. In order to overcome this predicament, non-native Chinese learners need to see a concrete connection between the classroom language and the real social environment, thus, the role of the teacher is instrumental in this process and endeavour. With this percept in mind, this study was designed as a task-based teaching activity, in which 75 thirdlevel non-native Chinese learners in UiTM Perlis stepped out of the classroom to engage in simple communication with native Chinese speakers. Through questionnaire survey and introspection records, this paper analyses and identifies the situation and problems faced by this group of learners when they communicate with native Chinese speakers for the first time, including psychological barriers and operational difficulties. The paper also explores the influence and effect of TBLT on learners' communication readiness and anxiety. The study found that in this framework, learners begin to realise the importance of language practice, experienced reduced communicative anxiety and increased confidence, thus the seed of interaction with the Chinese society is sowed for successful germination.